Wheat Variety Yield Response to Nitrogen and Sulfur Rates During the 2019–2020 Growing Season - B. R. Jaenisch; T. Wilson; N. Nelson; M. Guttieri; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
Early spring visual sulfur (S) deficiency symptoms are increasingly a concern for Kansas wheat growers, but the extent of yield limitation due to S deficiencies and its interaction with nitrogen (N) supply is not well quantified in this environment. Our objective was to evaluate the responses of three wheat varieties to the interaction of N and S rates. The experiment was conducted in four Kansas locations during the 2019–2020 winter wheat growing season: Ashland Bottoms, Argonia, Belleville, and Hutchinson. These locations were selected to provide a range in soil textures and organic matter content, as these variables might impact the crop’s response to the S rate. All results are discussed, but only those for Ashland Bottoms and Belleville, the most contrasting sites in terms of yield potential and soil organic matter content, are shown. Treatments were arranged as a complete factorial structure with a split-split-plot design. Variety was the whole plot, N was the sub-plot, and S was the sub-sub plot. Nitrogen rates were 50, 100, and 150% of the Kansas State University Soil Testing Lab recommendations for a 60 bushel per acre yield, and S rates were 0, 10, 20, and 40 pounds of S per acre. Wheat varieties evaluated were Zenda, SY Monument, and LCS Mint. Increasing N rates improved grain yield at all locations. The yield increase depended on the S rate at Ashland Bottoms (i.e., treatments not receiving S were non-responsive to N) but not at the remaining locations. Wheat varieties differed in grain yield at all locations regardless of N rate except for Argonia, where Zenda increased yields linearly with increases in N rate, whereas the remaining varieties showed a linear-plateau response. Increases in N rate also increased protein concentration at all locations, and this increase depended on S rate at three locations. Varieties differed in protein concentration at all locations, and this difference depended on the N rate in Argonia. Our results suggest that winter wheat response to the interaction between N and S fertilizer rates is location-specific, with greater chances of response in soils with sandier texture and lower organic matter contents.
Keywords: sulfur; nitrogen; wheat; Triticum aestivum L.; fertility; ratio; protein